1997
DOI: 10.1074/jbc.272.20.13390
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Cleavage of the Vascular Endothelial Growth Factor 189-Amino Acid Form by Urokinase Is Required for Its Mitogenic Effect

Abstract: Alternative splicing of vascular endothelial growth factor (VEGF) mRNA results in three distinct molecular forms of 121 or 165 (V165) amino acids that are released in the conditioned medium of cultured cells and one longer isoform of 189 amino acids (V189) that remains cell-associated. V189 has been expressed in wild type CHO-K1 cells and in glycosaminoglycan-deficient pgsA-745 Chinese hamster ovary (CHO) mutant cells. It could be released from CHO-K1 cell membranes by heparin or a synthetic peptide designed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
190
1
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(201 citation statements)
references
References 38 publications
8
190
1
2
Order By: Relevance
“…Cell culture trays were from Costar. Recombinant human V165 and V189 were synthesized in Sf9 cells infected with a recombinant baculovirus containing the V165 or V189 cDNA and purified by cation exchange and heparin affinity chromatography (18). Two molecular species were purified from V189-infected Sf9 cells: the 50-kDa native V189 and the 38-kDa matured V189.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell culture trays were from Costar. Recombinant human V165 and V189 were synthesized in Sf9 cells infected with a recombinant baculovirus containing the V165 or V189 cDNA and purified by cation exchange and heparin affinity chromatography (18). Two molecular species were purified from V189-infected Sf9 cells: the 50-kDa native V189 and the 38-kDa matured V189.…”
Section: Methodsmentioning
confidence: 99%
“…The binding domains of VEGF to Flt-1 and KDR/Flk-1 have been identified as the sequences 63-67 and 82-86, respectively (17). We recently demonstrated that native V189 binds to Flt-1 but requires a cleavage by urokinase located within the exon 6-encoded sequence to bind to KDR/Flk-1 and to exert a mitogenic effect on vascular endothelial cells (18). However the mitogenic effect of the shorter form generated by plasmin cleavage between Arg 110 and Ala 111 was reduced 10 -100-fold as compared with that of urokinase-matured V189 (18) or V165 (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of angiogenesis that occurred in AdmATFtreated mice might also have resulted from a concurrent action of ATF in hampering the bioavailability of angiogenic factors. [21][22][23][24][25] Because the dialogue between cancer and endothelial cells is of a 'symbiotic' nature, 2 ATF therapy may be particularly relevant because of its potential to target both the tumoral and endothelial compartments.…”
Section: Figure 6 Intratumoral Injection Of Admatf Inhibits Llc Tumormentioning
confidence: 99%
“…Finally, uPA and plasmin activate morphogenic or angiogenic factors such as VEGF, HGF, FGFs and TGF␤, further supporting cell-associated uPA in controlling cell migration and angiogenesis. [21][22][23][24][25] The relevance of targeting uPA and uPAR for cancer therapy is supported by epidemiological studies in which high level expression of uPA and uPAR are correlated with a poor prognosis in a number of malignancies, including ovarian, breast, gastric, brain and lung cancer. [26][27][28][29][30][31] Clinical observations also indicate the presence of enhanced uPA activity at the invasive edge of the tumors.…”
Section: Introductionmentioning
confidence: 99%